Chemical Ecology of the Benthic Dinoflagellate Genus Ostreopsis: Review of Progress and Future Directions - Pavaux, Anne-Sophie; Berdalet, Elisa; Lemée, Rodolphe (Frontiers in Marine Science, 2020)
The genus Ostreopsis includes some species that produce high biomass blooms and/or synthesize toxic compounds that can be transferred through the marine food webs or aerosolized causing ecological, human health and socio-economic impacts. Ostreopsis species are increasing their biogeographic distribution from tropical to more temperate waters and causing recurrent blooms in certain coastal areas, thus constituting an emerging concern worldwide. The proliferation capacity of Ostreopsis is due to a complex and poorly understood combination of multiple factors, and may be a paradigm of chemical ecology reviewed here. A first section summarizes the basic knowledge on the different Ostreopsis species, the toxins they produce and the described foodborne and airborne effects of Ostreopsis toxins on humans. Secondly, direct and indirect interactions between Ostreopsis species and their environment are reviewed. Mucopolysaccharide substances produced by the cells to attach to different substrates appear to be a key element on the chemical ecology and requires further study. However, this research is challenged by technical limitations to conduct ecologically realistic and harmonized studies where organisms can be in direct contact with Ostreopsis cells, their mucus and/or the released extracellular toxic compounds. Understanding the transfer mechanisms of these substances within the food web, potentially affecting humans is critical and requires further study with new analytical tools. Still, the progress in knowledge achieved in the last years, combined with experimental and field studies using cutting edge methods will facilitate to address the open questions on the chemical ecology of Ostreopsis and understand its bloom dynamics now, and under future climate and anthropogenic change scenarios.